Acetaldehyde-derived advanced glycation end-products promote alcoholic liver disease. - Nobuhiko Hayashi; Joseph George; Masayoshi Takeuchi; Atsushi Fukumura; Nobuyuki Toshikuni; Tomiyasu Arisawa; Mikihiro Tsutsumi (PLoS ONE, 2013)
Chronic ingestion of ethanol increases acetaldehyde and leads to the production of acetaldehyde-derived advanced glycation end-products (AA-AGE). We evaluated the toxicity of AA-AGE on hepatocytes and studied the role of AA-AGE in the pathogenesis of alcoholic liver disease (ALD).Rat hepatocyte cultures were treated with N-ethyllysine (NEL) or AA-AGE and the cell viability was evaluated using MTT assay. Male Wistar rats were fed with liquid diet containing 5% ethanol for 8 weeks following normal diet for another 12 weeks. A group of animals was sacrificed at 4th, 6th, and 8th week and the remaining animals at 12th, 14th, 16th, 18th, and 20th week. The liver sections were stained for AA-AGE and 4-hydroxy-2-nonenal (4-HNE). Liver biopsy obtained from ALD patients was also stained for AA-AGE and 4-HNE.Hepatocyte viability was significantly reduced in cultures treated with AA-AGE compared to NEL treated or control cultures. Severe fatty degeneration was observed during chronic administration of ethanol increasing from 4-8 weeks. The staining of AA-AGE and 4-HNE was correlated with the degree of ALD in both rat and human. In rats, hepatic fatty degeneration was completely disappeared and the staining for both AA-AGE and 4-HNE returned to normal at 12th week of abstinence. Staining for AA-AGE and 4-HNE was completely absent in normal human liver.The data demonstrated that AA-AGE is toxic to hepatocytes, but not NEL. Chronic ethanol ingestion produces AA-AGE and reactive oxygen species that contribute to the pathogenesis of ALD. Abstinence of alcohol results in complete disappearance of both AA-AGE and 4-HNE along with fatty degeneration suggesting that AA-AGE plays a significant role in the pathogenesis of ALD.